Auguste de Saint Hilaire e a civilização indígena: conquista ou filantropia? - Gomes, Rafael Augusto (2016)
This article seeks to understand how the traveller and naturalist Auguste de Saint-Hilaire characterized the American people and tried to incorporate them to the 'civilized' societies at the beginning of the XIX century. During that time, the European conception of 'mankind' was being reworded under the impact of the Lights Philosophy and the scientific expeditions. In order to interpret his reports we have used the Chartier analysis of the representations created by the author, looking for indigenous representations as well as the civilizing strategies made up by the French naturalist. We deeply believe that the conception of 'mankind' dialogued with the Philanthropic civilization ideals of that period.